Guideline summary review: an evidence-based clinical guideline for the diagnosis and treatment of degenerative lumbar spondylolisthesis - Matz, Paul G.; Meagher, R.J.; Lamer, Tim; Tontz, William L.; Annaswamy, Thiru M.; Cassidy, R. Carter; Cho, Charles H.; Dougherty, Paul; Easa, John E.; Enix, Dennis E.; Gunnoe, Bryan A.; Jallo, Jack; et al. (The spine journal, 2016)
The North American Spine Society's (NASS) Evidence-Based Clinical Guideline for the Diagnosis and Treatment of Degenerative Lumbar Spondylolisthesis features evidence-based recommendations for diagnosing and treating degenerative lumbar spondylolisthesis. The guideline updates the 2008 guideline on this topic and is intended to reflect contemporary treatment concepts for symptomatic degenerative lumbar spondylolisthesis as reflected in the highest quality clinical literature available on this subject as of May 2013. The NASS guideline on this topic is the only guideline on degenerative lumbar spondylolisthesis included in the Agency for Healthcare Research and Quality's National Guideline Clearinghouse (NGC). The purpose of this guideline is to provide an evidence-based educational tool to assist spine specialists when making clinical decisions for patients with degenerative lumbar spondylolisthesis. This article provides a brief summary of the evidence-based guideline recommendations for diagnosing and treating patients with this condition. A systematic review of clinical studies relevant to degenerative spondylolisthesis was carried out. This NASS spondyolisthesis guideline is the product of the Degenerative Lumbar Spondylolisthesis Work Group of NASS' Evidence-Based Guideline Development Committee. The methods used to develop this guideline are detailed in the complete guideline and technical report available on the NASS website. In brief, a multidisciplinary work group of spine care specialists convened to identify clinical questions to address in the guideline. The literature search strategy was developed in consultation with medical librarians. Upon completion of the systematic literature search, evidence relevant to the clinical questions posed in the guideline was reviewed. Work group members used the NASS evidentiary table templates to summarize study conclusions, identify study strengths and weaknesses, and assign levels of evidence. Work group members participated in webcasts and in-person recommendation meetings to update and formulate evidence-based recommendations and incorporate expert opinion when necessary. The draft guidelines were submitted to an internal peer review process and ultimately approved by the NASS Board of Directors. Upon publication, the Degenerative Lumbar Spondylolisthesis guideline was accepted into the NGC and will be updated approximately every 5 years. Twenty-seven clinical questions were addressed in this guideline update, including 15 clinical questions from the original guideline and 12 new clinical questions. The respective recommendations were graded by strength of the supporting literature, which was stratified by levels of evidence. Twenty-one new or updated recommendations or consensus statements were issued and 13 recommendations or consensus statements were maintained from the original guideline. The clinical guideline was created using the techniques of evidence-based medicine and best available evidence to aid practitioners in the care of patients with degenerative lumbar spondylolisthesis. The entire guideline document, including the evidentiary tables, literature search parameters, literature attrition flow chart, suggestions for future research, and all of the references, is available electronically on the NASS website at https://www.spine.org/Pages/ResearchClinicalCare/QualityImprovement/ClinicalGuidelines.aspx and will remain updated on a timely schedule.